The role of beluntas (pluchea indica less.) leaf extract in preventing the occurrence of fibroblasts hyperproliferation: An in vitro preliminary study - Sakti Charlia Maharani; Indah Julianto; Suci Widhiati (PAGEPress Publications, 2019)
Beluntas (Pluchea indica Less.) is a herbal plant which contains variety of benefits. Quercetin, one of flavonoid, is the most bioactive agent in beluntas leaf. Collagen inhibition by quercetin may modulate extracellular matrix deposition and inhibit the formation of hypertrophic scar. This was an in vitro study with senescent fibroblasts to determine the role of beluntas leaf extract in preventing the occurence of fibroblasts hyperproliferations. There were 4 groups were stained by anti-collagen I antibodies and secondary antibody. Flowcytometry analysis was done to measure the fibroblasts density. Anova test was performed with a value of p=0.000 (p<0.05). A post hoc analysis showed significant differences in the average decrease of fibroblasts that absorbs staining anti-collagen I antibody treatment group compared with the control group. There were significant effects of beluntas leaf extract in preventing the occurrence of fibroblasts hyperproliferations. Beluntas leaf extract with a concentration of 80 mol/L had the most significant effect on the fibroblasts density. Thus beluntas leaf extract has the ability in preventing the occurrence of fibroblasts hyperproliferation.